Home‐ and community‐level predictors of social connection in nursing home residents: A scoping review - Sara Clemens; Katelynn Aelick; Jessica Babineau; Monica Bretzlaff; Cathleen Edwards; Josie‐Lee Gibson; Debbie Hewitt Colborne; Andrea Iaboni; Dee Lender; Denise Schon; Ellen Snowball; Katherine S. McGilton; et al. (Health Science Reports, 2022)
Abstract Background and Aims Social connection is associated with better physical and mental health and is an important aspect of the quality of care for nursing home residents. The primary objective of this scoping review was to answer the question: what nursing home and community characteristics have been tested as predictors of social connection in nursing home residents? The secondary objective was to describe the measures of social connection used in these studies. Methods We searched MEDLINE(R) ALL (Ovid), CINAHL (EBSCO), APA PsycINFO (Ovid), Scopus, Sociological Abstracts (ProQuest), Embase and Embase Classic (Ovid), Emcare Nursing (Ovid), and AgeLine (EBSCO) for research that quantified associations between nursing home and/or community characteristics and resident social connection. Searches were limited to English‐language articles published from database inception to search date (July 2019) and update (January 2021). Results We found 45 studies that examined small‐scale home‐like settings (17 studies), facility characteristics (14 studies), staffing characteristics (11 studies), care philosophy (nine studies), and community characteristics (five studies). Eight studies assessed multiple home or community‐level exposures. The most frequent measures of social connection were study‐specific assessments of social engagement (11 studies), the Index of Social Engagement (eight studies) and Qualidem social relations (six studies), and/or social isolation (five studies) subscales. Ten studies assessed multiple social connection outcomes. Conclusion Research has assessed small‐scale home‐like settings, facility characteristics, staffing characteristics, care philosophy, and community characteristics as predictors of social connection in nursing home residents. In these studies, there was no broad consensus on best approach(es) to the measurement of social connection. Further research is needed to build an evidence‐base on how modifiable built environment, staffing and care philosophy characteristics—and the interactions between these factors—impact residents' social connection.